(untitled) (Journal of the College of Education for Women, 2019)
This study Studied Ministry of Hamdy Al-Buchachy(the first)and explain the features ofthis Ministry in a critical time in the history of Iraq. The second world war had began and itsend had reached .The political situation in Iraq is so complicated. The Ministry had mademany things. The Ministry had situated in internal and external complicated time. Thesituation in Iraq was so difficult, therefore the recommendor (Abdul-Ilah)asked Hamdy Al-Bachachy to make be the head of the new governments Al-Bachachy had made irrelevantgovernment, thus it didn’t last more than three months and the British governorate and ofdirect in terference in Iraq who worked to reduce the Iraqi army and the Minister of Defencerefused that because of the troubles in the north of Iraq(Barzan movement).It worleedhord toimprove the internal product and find solutions to the problems of the Iraqi people. In theexternal issue the Ministry participated in some of the conferences and international meetingsthat related to economy and finance and making diplomatic relationships with the socialcountries .as well as the other countries.It worked to develop the ability of governorate istituties especially in management andworker and increasing the number of employers in the Ministries that home a direct relationship with the life of citizens. Thus some of the critics against their Ministry is that itlimited the general freedom and democratic freedom so it didn’t give the freedom to politicalparties and the press that represent her.